Factors affecting citizen participation in village assembly in Akeri and Patandi villages in Meru district council - Msofe, Zaituni (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Management as a requirement for award of the Master’s Degree in Public Administration (MPA) offered by Mzumbe University